An investigation of the endoplasmic reticulum stress in obesity exposure in the prenatal period - Tufekci, Kiymet Kubra; Tatar, Musa; Terzi, Funda; Bakirhan, Elfide Gizem (Elsevier BV, 2023)
Exposure to maternal obesity has been shown to make offspring more prone to cognitive and metabolic disorders later in life. Although the underlying mechanisms are unclear, the role of endoplasmic reticulum (ER) stress in the fetal programming process is remarkable. ER stress can be activated by many chronic diseases, including obesity and diabetes. Therefore, our study aimed to investigate the role of ER stress caused by maternal diet-induced obesity in the offspring hippocampus. We also evaluated the protective effect of N-acetylcysteine (NAC) against ER stress.A rat obesity model was created by providing a high-fat (60 % kcal) diet. N-acetylcysteine (NAC) was administered at a dosage of 150 mg/kg via the intragastric route. The animals were mated at the age of 12 weeks. The same diet was maintained during pregnancy and lactation. The experiment was terminated on the postnatal 28th day, and the offspring's brain tissues were examined. Immunohistochemical staining for ER stress markers was performed on sections taken from tissues after routine histological procedures.The results revealed increased GRP78, PERK, and eIF2α immunoreactivities in the hippocampal dentate gyrus (DG) and cornu ammonis 1 (CA1) regions in the obese group offspring, while the expression of those markers in those regions normalized with NAC supplementation (p < 0.01). Statistical analysis of XBP1 immunoreactivity H-scores revealed no difference between the study groups (p > 0.05).These results suggest that exposure to obesity during the prenatal period may cause increased ER stress in hippocampal neurons, which have an important role in the regulation of learning, memory and behavior, and this may contribute to decreased cognitive performance. On the other hand, NAC stands out as an effective agent that can counteract hippocampal ER stress.
Keywords: Pregnancy; Humans; Animals; Infant; Female; Obesity; Endoplasmic Reticulum Stress; Endoplasmic Reticulum Chaperone BiP; Hippocampus; Rats; Acetylcysteine; 2. Zero hunger